Femoral Shaft Fractures in Children Age 1-5 years Treated with Single Leg Walking Spica, Our Experience (Journal of Pakistan Orthopaedic Association, 2023)
Introduction: Femoral shaft fractures are common in children. These fractures are classified according to the area of fracture involved. The treatment of femoral shaft fractures depends upon the age of patient. In children less than 6 years of age, hip spica is the treatment of choice.Methods: this prospective study was conducted in orthopedic unit DHQ hospital Khar Bajaur and Orthopedic department Peshawar Medical College, Peshawar from July 2020 till June 2021. All patients fulfilling the inclusion criteria were enrolled in the study. Single leg hip spica were applied by two experienced orthopedic surgeons. Followup was done. Spica was removed after 6 weeks.Results: A total of 31 patients were enrolled in the study. Mean age was 3.8 years. 58% patients were male and 42% were female. 58.1% had middle 1/3rd femur shaft fracture. LLD was the most common complication (9.7%).Conclusion: Single leg hip spica is simple, efficient and cost effective treatment for children less than 5 years of age.